Influence of previous gastrectomy on postoperative bile leakage after laparoscopic liver resection - Takao Ide; Kotaro Ito; Tomokazu Tanaka; Hirokazu Noshiro (BMC Surgery)
Abstract Background Postoperative bile leakage (POBL) is a common cause of major morbidity following liver resection. Although the use of laparoscopy for liver surgery has expanded rapidly, POBL has been poorly described in patients undergoing laparoscopic liver resection (LLR). This study aimed to identify the risk factors for POBL after LLR. Methods We enrolled 510 consecutive patients who underwent LLR for hepatic tumors between January 2009 and December 2023. POBL was defined according to the International Study Group of Liver Surgery, and its incidence, consequences, clinicopathological factors, and surgical details were evaluated retrospectively. Risk factors for POBL were determined using a multivariable logistic regression analysis. Results POBL occurred in nine patients (1.8%). POBL was significantly associated with advanced age (81 vs. 72 years, p = 0.005), history of gastrectomy (3/9 vs. 25/501, p = 0.002), high incidence of postoperative complications (9 vs. 26, p = 0.001), and prolonged hospital stay (57 vs. 8 days, p = 0.001). In the multivariable analysis, POBL was significantly associated with a history of gastrectomy (OR 7.71, 95% CI 1.744–34.043, p = 0.007). In the management of POBL, all patients were successfully treated with percutaneous drainage alone or with additional treatment using endoscopic nasobiliary drainage. Conclusion Previous gastrectomy was an independent risk factor for POBL in patients undergoing LLR.